(untitled) (Journal of Interdisciplinary Insights, 2024)
This study aimed to diagnose parental burnout and identify its underlying causes, subsequently providing recommendations for prevention. The research was conducted in two stages: initially, parental burnout levels among parents in Darkhan-Uul province were assessed, revealing an overall burnout level below average, although a subset of parents exhibited high levels of burnout. This initial diagnosis is crucial as it enhances the potential for early intervention and prevention. In the second stage, interviews were conducted to explore the causes of parental burnout, identifying common factors such as overworking, child behavior problems, sleep and eating disorders, children’s health issues, and being a new parent. The findings highlight the significance of diagnosing parental burnout, understanding its causes, and implementing effective preventive measures. Additionally, the study emphasizes the need for ongoing research to address parental burnout comprehensively over the long term, thereby supporting the mental health and well-being of both parents and their children.